Bukancumasedih: Program Psikoedukasi Digital tentang Depresi pada Remaja melalui Media Sosial Instagram - Satyalaksmi Aisya Kautsarani; Vicha Dewi Setia Ningrum; Fadia Chika Bonita; Endang Retno Surjaningrum; Ika Yuniar Cahyati (Sarau Institute, 2026)
Depressive disorders among high school students have become an urgent mental health issue, caused by various academic and social challenges, as well as the effects of bullying. Unfortunately, many students still struggle to recognize the early signs and are reluctant to seek help due to stigma. The “Bukancumasedih” initiative emerged as a promotive and preventive psychoeducational effort, utilizing interactive visual content via the Instagram account @bukancumasedih to efficiently reach adolescents. The program’s implementation approach included the creation of planned educational content, the administration of a pre-test and post-test, and the analysis of audience engagement. The results of this program show an increase in participants’ understanding, reflected in a rise in the acreage scores from 3.50 (pre-test) to 3.77 (post-test). All presented materials successfully exceeded interaction standards by receiving at least 10 likes per post. This initiative demonstrates that Instagram-based psychoeducation is effective in raising mental health awareness among adolescents through a casual and accessible approach.